The Effect of Video-Assisted Education on Knee Function and Quality of Life after Total Knee Replacement: A Randomized Controlled Trial - Volkan Öztuna; Bahar Taşdelen; Servet Can Dönmez; Recep Ünal; Bedriye Biricik; Gülay Altun Uğraş (Atatürk University, 2024)
Objective: This study aims to investigate the effect of video-assisted patient education (VPE) on knee functions, quality of life (QoL) and decrease complications in total knee replacement (TKR) patients.Methods: This study is designed as a prospective, parallel, two-arm, randomized clinical trial. It included 44 patients who underwent elective TKR at an orthopedics and traumatology clinic. The VPE group received VPE including early postoperative care for TKR, activities of daily living, and gradual exercise program in addition to the existing routine care at the clinic. The control group received only routine care. The results were collected with Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Short Form-36 (SF-36) scores measured at baseline, 1st and 3rd months after TKR. Results: The mean scores of the VPE group on the pain, stiffness, and physical function of the WOMAC were significantly lower in 3rd month after TKR than the control group. The VPE group had significantly higher scores than the control group on SF-36 of all subcategories except pain, emotional role, and mental health in 3rd month after TKR.Conclusion: The VPE can improve knee function and QoL in TKR patients. Nurses can use the VPE method in patients to improve knee functions and QoL after TKR.